(untitled) (Medico Legal Update, 2021)
Background: ST-Elevation Myocardial Infarctionis a time-sensitive emergency condition. Thus, guidelines recommended 90 minutes or less for door-to-balloon time at a percutaneous coronary intervention-capable hospital and with in 120 minutes or less if transferred from per cutaneous coronary intervention-Uncapable Hospital. The main objective was to evaluate the recommended time needed forreperfusion therapy particularly percutaneous coronary intervention inpatients with ST-Elevation Myocardial Infarctionat King Abdullah Medical City. Method and Results: A retrospective single center study. Data were obtained from 47 patients records diagnosed with ST-Elevation Myocardial Infarction and treated with percutaneous coronary interventionat King Abdullah Medical Cityfrom Jan 2018 through March 2019. About 36.4% of patients received percutaneous coronary intervention in more than 90 Minutes eventhough they arrived directly at King Abdullah Medical City. For patients who were transferred to King Abdullah Medical City, 63.9% of those patients did not achieve the recommended door-to-balloon time. Conclusion: High percentage of patients with ST-Elevation Myocardial Infarctionat King Abdullah Medical City did notreceive percutaneous coronary intervention within the recommended timeline.